ANALYSIS OF THE CONCEPT OF INDEPENDENCE AND PROFESSIONALISM OF INDONESIAN ULEMA COUNCIL TOWARDS HALAL GUARANTEE CERTIFICATION ON PROCESSED FOOD INDUSTRY IN WEST JAVA - Neng Yani Nurhayani; Sarip Muslim (International Journal of Nusantara Islam, 2019)
This study aims to analyze the mechanism of Halal Guarantee Certification  publication in the food processing industry in West Java; and the application of the principle of independence and professionalism of The Indonesian Ulema Council (MUI) in awarding Halal Guarantee Certification for processed food industries in West Java. Additionally, this study is a field research using a qualitative approach. The mechanism of awarding Halal Guarantee Certification  begins with the company stating written objectives of the certification's implementation for the company regarding the rules outlined by The Research Institution on Food, Drug, and Cosmetics (LPPOM) and explaining the scope of application of guarantee systems in the corporate environment; begun with purchasing, receiving materials, production lines, storage of materials and products, transportation and distribution, as well as food displaying and serving (for restaurants to be assessed by LPPOM). The independence aspect is not only identified through being independent at organizing an institution; moreover, the careful consideration of expertise, field data, and also appearance must be the main indicators. The application of the professionalism principle, by The Indonesian Ulema Council in awarding Halal Guarantee Certification for the processed food industries in West Java, can be indicated through the method of assessing processed food industry products. As the result, The Ulema Council has been able to carry out excellent and appropriate coordination by giving this role to LPPOM.